Inhibition of NAADP signalling on reperfusion protects the heart by preventing lethal calcium oscillations via two-pore channel 1 and opening of the mitochondrial permeability transition pore. (22nd September 2015) - Davidson, Sean M.; Foote, Kirsty; Kunuthur, Suma; Gosain, Raj; Tan, Noah; Tyser, Richard; Zhao, Yong Juan; Graeff, Richard; Ganesan, A.; Duchen, Michael R.; Patel, Sandip; Yellon, Derek M.
Abstract: Aims: In the heart, a period of ischaemia followed by reperfusion evokes powerful cytosolic Ca 2+ oscillations that can cause lethal cell injury. These signals represent attractive cardioprotective targets, but the underlying mechanisms of genesis are ill-defined. Here, we investigated the role of the second messenger nicotinic acid adenine dinucleotide phosphate (NAADP), which is known in several cell types to induce Ca 2+ oscillations that initiate from acidic stores such as lysosomes, likely via two-pore channels (TPCs, TPC1 and 2). Methods and results: An NAADP antagonist called Ned-K was developed by rational design based on a previously existing scaffold. Ned-K suppressed Ca 2+ oscillations and dramatically protected cardiomyocytes from cell death in vitro after ischaemia and reoxygenation, preventing opening of the mitochondrial permeability transition pore. Ned-K profoundly decreased infarct size in mice in vivo . Transgenic mice lacking the endo-lysosomal TPC1 were also protected from injury. Conclusion: NAADP signalling plays a major role in reperfusion-induced cell death and represents a potent pathway for protection against reperfusion injury.